2017
DOI: 10.1371/journal.pntd.0005526
|View full text |Cite
|
Sign up to set email alerts
|

In the hunt for genomic markers of metabolic resistance to pyrethroids in the mosquito Aedes aegypti: An integrated next-generation sequencing approach

Abstract: BackgroundThe capacity of Aedes mosquitoes to resist chemical insecticides threatens the control of major arbovirus diseases worldwide. Until alternative control tools are widely deployed, monitoring insecticide resistance levels and identifying resistance mechanisms in field mosquito populations is crucial for implementing appropriate management strategies. Metabolic resistance to pyrethroids is common in Aedes aegypti but the monitoring of the dynamics of resistant alleles is impeded by the lack of robust ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
132
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(142 citation statements)
references
References 64 publications
10
132
0
Order By: Relevance
“…Similarly, CCEae3A and 6A have been associated with temephos resistance in an A. aegypti strain for Thailand that was also resistant to pyrethroids (Poupardin et al , ). Although amplification of these CCE clusters are a possible mechanism to overexpress enzymes that metabolize insecticides, our study and others (Faucon et al , ; ) have also identified allele variants within these genes. The roles of these nonsynonymous mutations in catalytic activity is of great interest.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Similarly, CCEae3A and 6A have been associated with temephos resistance in an A. aegypti strain for Thailand that was also resistant to pyrethroids (Poupardin et al , ). Although amplification of these CCE clusters are a possible mechanism to overexpress enzymes that metabolize insecticides, our study and others (Faucon et al , ; ) have also identified allele variants within these genes. The roles of these nonsynonymous mutations in catalytic activity is of great interest.…”
Section: Discussionmentioning
confidence: 51%
“…Because previous studies focused mostly on gene expression, we compared our list of genes with significant SNPs with 22 studies that had measured gene expression in mosquitoes exposed to sublethal doses of insecticides (Poupardin et al , ; ; ; Riaz et al , ; David et al , ). We also included published articles that compared insecticide‐resistant versus susceptible strains (Strode et al , ; ; Marcombe et al , ; Saavedra‐Rodriguez et al , ; ; David et al , ; Reid et al , ; Estep et al , ) and, most recently, allelic variants (David et al , ; Dusfour et al , ; Faucon et al , ; ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A handful of P450s, especially from CYP6 and CYP9 subfamilies, confer pyrethroids resistance in Aedes aegypti populations; eg CYP6BB2 , CYP6M11 and CYP6N12 in field mosquitoes from three French overseas territories (Dusfour et al ., ), CYP9J27 , CYP6CB1 , CYP9J26 and CYP9M4 in Malaysian field populations (Ishak et al ., ), and CYP6Z8 in laboratory strains (Chandor‐Proust et al ., ). In our study, the DR‐6 was enriched in P450s, some of which are orthologues of genes implicated in pyrethroid resistance in Anopheles gambiae , A. funestus and A. aegypti (Riaz et al ., ; Faucon et al ., ). Both parents and mapping populations detected L1014F mutation in the para‐type sodium channel gene (Zou et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Faucon et al . (, ) reported that CYP6BB2 showed a significant positive correlation between the transcription levels and copy number variations associated with pyrethroids resistance. Taken together, we predict that CYP6BB4 played a role in pyrethroid resistance and was expected to become a potential marker to monitor and predict the pyrethroid resistance in mosquito populations.…”
Section: Resultsmentioning
confidence: 99%
“…Should encoded enzymes be functionally impaired reduced pesticide detoxification could occur. Positive effects of nonsynonomous SNVs on metabolic resistance to pyrethroids are supported by a recent investigation into the genomic basis of metabolic resistance in A. aegypti (Faucon et al ., ). Those authors report nonsynonymous variations within the substrate recognition site of P450s that are more abundant in resistant strains of Aedes .…”
Section: Discussionmentioning
confidence: 97%